Semiotic representation in Mathematics: history, epistemology, learning Registros de representação semiótica em matemática: história, epistemologia, aprendizagem - Cláudia Regina Flores (Universidade Estadual Paulista, 2008)
Since the works of Raymond Duval, the question regarding the role of records of semiotic representation in the learning of Mathematics has been an object of research. There is no doubt that records of semiotic representation are essential for the creation of mathematical objects, as well as for the learning of Mathematics. The subject of this text is, therefore, to offer some reflections on the way of thinking which gives foundation to this hypothesis. How did the idea of representation, particularly semiotic representation, become the model for the acquisition of knowledge within a specific line of thought? It can be said that the representation records theory, elaborated by Duval, for the learning of Mathematics, has modern thought as a base: a cognoscenti subject, a cognoscible object and a dual theory of signs. This analysis becomes particularly important for making possible a deeper reflection, especially in the education of Mathematics teachers, in regard to the learning theories which are employed, as well as the formation of the knowledge which is taught in Mathematics. Key words: Representation. Semiotics. History of Mathematics. Mathematics Education. A partir dos estudos de Raymond Duval, a questão do papel dos registros de representação semiótica para a aprendizagem matemática tem sido foco de pesquisas, em educação matemática. Não há dúvida de que os registros de representação semiótica são essenciais tanto para a criação de objetos matemáticos como para a sua apreensão. A questão neste artigo é, então, trazer algumas reflexões sobre o modo de pensamento que fundamenta esta hipótese. Como a idéia de representação, particularmente de representação semiótica, se constituiu como o modelo para aquisição do conhecimento dentro de um regime de pensamento? Pode-se afirmar que o estudo sobre os registros de representação semiótica, empreendido por Duval, tem como base o pensamento moderno: um sujeito cognoscente, um objeto cognoscível e uma teoria dual dos signos. Esta análise se faz importante por possibilitar reflexões profundas, particularmente, na formação de professores de matemática, acerca das teorias de aprendizagem que se pratica, bem como da própria constituição dos saberes que se ensina em matemática. Palavras-chave: Representação. Semiótica. História da Matemática. Educação Matemática.